Case report: First diagnosis of Fabry disease in North Macedonia in a patient presenting with kidney failure on hemodialysis - Gjorgjievski, Nikola; Karanfilovski, Vlatko; Arsov, Todor; Vidimliski, Pavlina Dzekova; Andreevska, Galisna Severeova; Selim, Gjulshen; Dejanov, Petar; Jordanova, Vasilena; Marinova, Ivelina; Paskalev, Emil; Nikolov, Igor G. (Frontiers in Genetics, 2024)
Introduction: Fabry disease is a rare X-linked lysosomal storage disease caused by αgalactosidase A (α-Gal A) deficiency. Reduced or absent enzyme activity causes progressive lysosomal accumulation of globotriaosylceramide (Lyso-Gb3) in various cells throughout the body, triggering inflammation and fibrosis.We present the first familial case with Fabry Disease in North Macedonia identified based on the clinical manifestations, and confirmed with enzyme, biomarker, and genetic tests. The index case in the family was a 43-year-old male undergoing hemodialysis therapy. He has had a chronic burning uncontrolled limb pain since childhood, intermittent abdominal cramps, anhidrosis, and hypertension. The constellation of the clinical presentation accompanied by similar symptoms in close family members prompted enzyme, biomarker, and genetic analyses for Fabry disease. Genetic testing identified a known pathogenic GLA missense variant c.443G>A or p.(Ser148Asn) in a hemizygous state. Subsequent family studies identified another hemizygous male and five heterozygous female carriers affected with this X-linked disorder.We report the identification of the first familial case with Fabry disease in North Macedonia and describe the phenotype associated with the Ser148Asn GLA variant. The higher awareness of this rare disease linked to continuous medical education is crucial for timely diagnosis and treatment.